Geophysical analysis at the Old Whaling site, Cape Krusenstern, Alaska, reveals the possible impact of permafrost loss on archaeological interpretation - Christopher B. Wolff; Thomas M. Urban (Polar Research, 2013)
The Old Whaling site at Cape Krusenstern, Alaska, has been the subject of contested interpretations stemming from an original theory proposed by J. Louis Giddings more than half a century ago. In an attempt to address recent suggestions that the occupational history is more complex than originally believed, the site was the subject of a non-invasive geophysical survey conducted by our team in 2011. The project served as a starting point for assessing the potential for archaeological remains at the site that had not been detected with previous investigations, and to gain a better understanding of site morphology. The investigation was implemented with two well-established geophysical methods, ground-penetrating radar (GPR) and magnetic gradiometry. The survey revealed no unequivocal evidence of additional occupations as has been recently suggested, but did reveal a dynamic site morphology that may have implications for archaeological interpretation.